Evaluation of the acid hydrolysis extraction factors and characterization of microcrystalline cellulose (mcc) from Theobroma cacao l. pod husks - Cacho, Julia Linnea T.
Theobroma cacao L., or cacao, is a small evergreen tree that provides an important source of revenue for smallholder farmers in East Asia. After harvest, over 70%-75% of the cacao fruit is discarded as cacao pod husks (CPH) and left to degrade, posing a significant waste management and disease prevention concern. CPH is an abundant and renewable source of cellulose, a precursor for microcrystalline cellulose (MCC), commonly utilized as a pharmaceutical excipient. The purpose of this research is to evaluate the acid hydrolysis extraction factors (acid temperature, acid hydrolysis time, and acid concentration) that affect the yield of MCC from Theobroma cacao L. pod husks using one-factor-at-a-time (OFAT) design and to characterize the physicochemical properties of the extracted MCC based on the Pharmacopeial standards. The highest percent yield of MCC was extracted from the following acid hydrolysis conditions: 70°C (80.31% ± 6.9) for 15 minutes (87.27% ± 0.73), using 2.0 N HCl concentration (91.21% ± 0.95). The extracted MCC from the optimum factors were within the acceptance criteria of the physicochemical evaluation and Pharmacopeial monograph testing except for the pH and residue on ignition tests. Fourier-transform infrared spectroscopy (FTIR) spectra of both the standard and the extracted MCC showed no difference in the observed significant peaks which confirmed the presence of the expected MCC functional groups in the sample.